SIGGRAPH Asia 2017 Technical Briefs 2017
DOI: 10.1145/3145749.3149423
|View full text |Cite
|
Sign up to set email alerts
|

Foveated instant preview for progressive rendering

Abstract: Progressive rendering, for example Monte Carlo rendering of 360 • content for virtual reality headsets, is a time-consuming task. If the 3D artist notices an error while previewing the rendering, he or she must return to editing mode, do the required changes, and restart rendering. Restart is required because the rendering system cannot know which pixels are affected by the change. We propose the use of eye-tracking-based optimization to significantly speed up previewing the artist's points of interest. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Ray tracing was used to render the foveal region and rasterization to render the peripheral region. To speed up previewing the artist's points of interest, Koskela et al [119,124] applied foveated rendering to progressive Monte Carlo rendering, which omits more than 90% of rays that must be traced in real time. Their user study demonstrated that the perceived convergence of the proposed method was 10× faster than that of a conventional preview, and participants rated the method to have only marginally more artifacts in areas where it had to start rendering from scratch.…”
Section: Multi-spatial Resolution Based Ray Tracingmentioning
confidence: 99%
“…Ray tracing was used to render the foveal region and rasterization to render the peripheral region. To speed up previewing the artist's points of interest, Koskela et al [119,124] applied foveated rendering to progressive Monte Carlo rendering, which omits more than 90% of rays that must be traced in real time. Their user study demonstrated that the perceived convergence of the proposed method was 10× faster than that of a conventional preview, and participants rated the method to have only marginally more artifacts in areas where it had to start rendering from scratch.…”
Section: Multi-spatial Resolution Based Ray Tracingmentioning
confidence: 99%
“…We extend our previous work [4] with an additional evaluation of the questionnaire presented to the participants of the user study, and an evaluation of how the participants assessed artifacts in the results.…”
Section: Introductionmentioning
confidence: 99%